2021
DOI: 10.3126/janr.v4i2.33712
|View full text |Cite
|
Sign up to set email alerts
|

Effect of integrated nutrient management on growth and yield of radish

Abstract: Integrated Nutrient Management (INM) is necessary to enhance sustainable yield in an eco-friendly way. A field experiment was conducted in the research field of Midwest Academy and Research Institute College of Live Sciences, Tulsipur, Dang from November 2018 to January 2019 to investigate the effect of integrated nutrient management on growth and yield of radish. Mino Early variety was used in the experiment. The experiment was laid out on Randomized Complete Block Design with four replications and 5 treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Similarly, at 60 DAS, the significantly maximum number of leaves (16.43) was recorded in treatment T13, which comprised 50% RDF along with poultry manure applied at a rate of 2.5 tons per hectare. These findings support the previous studies conducted by Basnet et al, (2021) and Subedi et al, (2018), which also reported the stimulatory effects of poultry manure NPK and FYM.…”
Section: Growth Parameterssupporting
confidence: 93%
“…Similarly, at 60 DAS, the significantly maximum number of leaves (16.43) was recorded in treatment T13, which comprised 50% RDF along with poultry manure applied at a rate of 2.5 tons per hectare. These findings support the previous studies conducted by Basnet et al, (2021) and Subedi et al, (2018), which also reported the stimulatory effects of poultry manure NPK and FYM.…”
Section: Growth Parameterssupporting
confidence: 93%
“…The highest grain yield, straw yield and biological yield was observed in treatment 75% RDN+25% RDN through poultry manure and it was statistically at par with 50% RDN+ 50% poultry manure, 100% RDN, 50% RDN+50% FYM and 75% RDN+ 25% FYM. Basnet et al [8] observed the highest germination percentage (77.00 %), plant height (13.27 cm) and yield (16.55 t ha -1 ) with treatment 50% recommended N through chemical fertilizer + 50% N through poultry manure while highest leaf numbers (10.40 PCS) observed in treatment 50% recommended N through chemical fertilizer + 50% N through vermicompost. Keeping in view the above facts, the present study was conducted to study the effect of different sources of nitrogen on growth, yield and yield attributes of rice crop.…”
Section: Introductionmentioning
confidence: 98%
“…Also, the result was in line with (Baitilwake et al, 2011) who observed poultry manure results higher fresh and dry yield of chinese cabbage and amaranthus. Poultry manure's ability to supply all 13 essential plant nutrients likely contributes superior root length, diameter and yield (Basnet et al, 2021).…”
Section: Yield Parametersmentioning
confidence: 99%